Ransomware Evolution: Techniques, Countermeasures, and Legal Implications - Patil, Pankaj Kautik (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
Ransomware has become one of the most significant cybersecurity threats of the modern digital age, evolving in complexity and scale over time. This document provides a comprehensive analysis of ransomware, beginning with its background and a review of existing literature to understand its origins and early objectives. It evaluates early ransomware attacks and key milestones that have shaped its evolution.The study further explores modern ransomware tactics, including double extortion, Ransomware-as-a-Service (RaaS), and the targeting of critical infrastructure. It delves into the role of cryptocurrency in facilitating anonymous ransom payments and examines sophisticated delivery mechanisms used by attackers. The broader impacts of ransomware, encompassing financial, operational, and reputational damages, are assessed, highlighting the urgency for effective countermeasures. Various mitigation strategies are analysed, along with the challenges faced in their implementation. Legal implications of ransomware attacks are also discussed, emphasizing the need for stronger regulatory frameworks and international collaboration. The document concludes by exploring future trends in ransomware and offers actionable recommendations to strengthen defences against this evolving threat.